APPLICATION OF MODEL-ELICITING ACTIVITIES (MEAs) FOR LEARNING MATHEMATICS BASED ON STUDENTS’ INITIAL MATHEMATICAL ABILITIES - Ibnu Imam Al Ayyubi; Irfan Suryana; Tommy Tanu Wijaya; Firda Noerzanah; Shoutika Nawadya Ikromi (El Midad, 2024)
This study aims to analyze the application of the Model-Eliciting Activities (MEAs) for learning mathematics based on students’ initial mathematical abilities and school origin. It was conducted at SDN Batujajar 3, SDN Sukamaju and SDS Yayasan Beribu by using a quantitative research approach. The research method used the survey method and Two Ways ANOVA test analysis to determine the relationship between students; initial mathematics learning outcomes, students’ origin school, and students’ initial mathematical abilities with a sample of 81 students. In this study, it was found that in learning using the Model-Eliciting Activities there were differences in students’ mathematics learning outcomes based on students’ school origin, students’ mathematics learning outcomes based on students’ initial mathematical abilities, and there was an interaction between school origin and students’ initial mathematical abilities in determining mathematics learning outcomes. In addition, the interaction that occurred shows that SDS Yayasan Beribu had better than SDN Batujajar 3 and SDN Sukamaju.